Non-Markovian dynamics of mixed fermionic-bosonic systems: Rotating-wave-approximation coupling - Sargsyan V. V. Vazgen Valerikovich; Adamyan G. G. Gurgen Grigorjevich; Antonenko N. V. Nikolay Viktorovich; Lacroix D . (2017, 2017)
Title screen